2004
DOI: 10.1007/s00018-004-4082-3
|View full text |Cite
|
Sign up to set email alerts
|

Differential distribution of TASK-1, TASK-2 and TASK-3 immunoreactivities in the rat and human cerebellum

Abstract: In this work, the distributions of some acid-sensitive two-pore-domain K+ channels (TASK-1, TASK-2 and TASK-3) were investigated in the rat and human cerebellum. Astrocytes situated in rat cerebellar tissue sections were positive for TASK-2 channels. Purkinje cells were strongly stained and granule cells and astrocytes were moderately positive for TASK-3. Astrocytes isolated from the hippocampus, cerebellum and cochlear nucleus expressed TASK channels in a primary tissue culture. Our results suggest that TASK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…The expression of the four subunits in large cells was not greatly influenced by deafening, which predominantly decreased their expression in small and medium sized cells. K 2p channel subunits have been previously identified in astrocytes (Gnatenco et al, 2002;Rusznak et al, 2004, Kindler et al, 2000 where they have been suggested to play a role in ionic homeostasis. Skatchkov et al (2006) reported that K 2p channel subunits are functionally expressed in retinal glial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of the four subunits in large cells was not greatly influenced by deafening, which predominantly decreased their expression in small and medium sized cells. K 2p channel subunits have been previously identified in astrocytes (Gnatenco et al, 2002;Rusznak et al, 2004, Kindler et al, 2000 where they have been suggested to play a role in ionic homeostasis. Skatchkov et al (2006) reported that K 2p channel subunits are functionally expressed in retinal glial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytes of hippocampus and cerebellum express TASK1 protein (Kindler et al, 2000;Millar et al, 2000;Kanjhan et al, 2004;Rusznak et al, 2004;Kim et al, 2007), but so far evidence of functional expression of acidand bupivacaine-sensitive TASK channels in these cells is lacking. The present study also failed at finding effects of bupivacaine after inhibiting Kir-and 4-AP-sensitive voltage-gated currents.…”
Section: Expression Of K 2p Channels By Hippocampal Astrocytesmentioning
confidence: 99%
“…TASK-1 staining was included because there are controversial reports of TASK-1 expression in astrocytes, as measured by immunocytochemistry (Kindler et al, 2000;Rusznák et al, 2004).…”
Section: Immunocytochemical Staining For Twik-1 Trek-1 and Task-1 Imentioning
confidence: 99%